Penghambatan Interaksi Eutektik Akibat Energi Kompresi dengan Penambahan Pati Jagung - Dwi Setyawan; Noorma Rosita; Diajeng Putri Paramita; Dicky Pratama (Jurnal Sains Farmasi & Klinis, 2018)
This research has been carried out to study inhibition of eutectic interaction which occurs on compressed binary mixture of ibuprofen-stearic acid by addition of corn starch. Corn starch was mixed into binary mixture of 40:60 (% b/b) ibuprofen-stearic acid with composition 10, 20, and 30% (w/w) and then compressed into tablet form. The physical characterization was conducted using tensile strength test, differential thermal analysis (DTA), powder X-ray diffraction (PXRD), Fourier transform infrared (FT-IR), and scanning electron microscope (SEM). According to tensile strength test, the value was reduced upon addition of 10 and 20% corn starch compared to the compressed binary mixture. Addition 20% corn starch to compressed binary mixture shifted the eutectic diffraction peaks with a decline in intensity during PXRD study. Thermal analysis of compressed binary mixture-20% corn starch exhibited an increase in eutectic point, and FT-IR spectrum was observed no difference compared to the compressed binary mixture. SEM analysis indicated that 20% corn starch addition was able to inhibit sintering phenomena by dispersed on particle’s surfaces. Physical characterizations result in the conclusion that corn starch can inhibit the eutectic interaction between ibuprofen and stearic acid upon compression